Is Optical Coherence Tomography a Useful Tool to Objectively Detect Actual Posterior Vitreous Adhesion Status?. (16th February 2016) - Bertelmann, Thomas; Goos, Christina; Sekundo, Walter; Schulze, Stephan; Mennel, Stefan
Abstract : Purpose . To objectively detect true posterior vitreous cortex (PVC) adhesion status using a commercially available swept-source OCT device (DRI OCT-1, Atlantis © ). Material and Methods . Case report, review of the literature, and methodical discussion of concepts to improve OCT-guided PVC imaging. Results . Standard OCT imaging misdiagnosed PVC adhesion status as totally detached in this case report when using a horizontal 6 mm scan only. Contrariwise imaging the same eye with a 12 mm horizontal scan, partial posterior vitreous detachment (PVD) and the presence of a bursa premacularis were clearly discernible. Besides a broader scan, specific scan patterns, highest resolution, and contrast sensitivity, an anterior-to-posterior adjusted scan through the entire vitreous as well as the detection of characteristic undulating aftermovements might enhance the capability of OCT imaging to detect true PVC adhesion status. Conclusions . Further developments are needed to address these issues and to establish OCT recordings as the standard and objective method of choice in PVC adhesion status imaging.